Evolution, Challenges, and Perspective in the Implementation of Projects with Renewable Energy Sources: Colombia Case - Rocha, Christian M. Moreno; Boiler, Jorge D. Melo; Pizarro, Samira M. Muñoz; Higuera, Leidy M. Mora; Conde, William R. Insignares (International Journal of Energy Economics and Policy, 2022)
This work quantifies the evolution in the implementation and development of renewable energies in Colombia, as well as evidence the current challenges and development prospects. The high demand for electricity in Colombia is increasing due to the great increase in population, industry and commerce, which generates greater energy consumption and as a consequence economic, social and environmental problems. The objective of this study was to analyze the behavior of the energy projects submitted to the Mining Energy Planning Group (UPME) during the last 15 years until July 2022, as well as to study the research areas with the highest performance. technology and the corresponding radiation intensity. In addition, it shows an historic information about the projects presented both not in force as of the date of closing of this investigation, classified according to their source, according to their range of power and according to its stage of implementation, finally, we made a synthesis of the new regulations governing the motivation and implementation of projects with renewable energy sources, being as this work a very good source of reference for further studies of the implementation of renewable energy sources in Colombia.